ANALISIS KUALITAS PRODUK, HARGA, DAN PROSES TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN PADA APLIKASI GOFOOD MARTABAK DJOERAGAN PEKANBARU - ,Aida Nursanti, Hafiz Savero ,Hj. Alvi Furwanti Alwie (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of Product, Price and Process on customer satisfaction through purchasing decisions. The population in this study were consumers of Djoeragan's martabak who had bought Djoeragan's martabak through the Gofood application in Pekanbaru. The number of samples taken in the study were 115 respondents. The data used in this study is primary from the results of the questionnaire. The data analysis tool used for hypothesis testing is path analysis with the Statistical Program for Social Science (SPSS) approach vertion 25. The results of this study state that: 1) Products have a significant effect on purchasing decisions; 2) Price has a significant effect on purchasing decisions; 3) The process has a significant effect on purchasing decisions; 4) Products have a significant effect on customer satisfaction through purchasing decisions; 5) Price has a significant effect on customer satisfaction through purchasing decisions; 6) The process has a significant effect on customer satisfaction through purchasing decisions; 7) purchasing decisions have a significant effect on customer satisfaction Keywords: Product, Price, Process, Customer Satisfaction, Purchase Decision